Effect of ethyl acetate aroma on viability of human breast cancer and normal kidney epithelial cells in vitro - Mohsin A. Khan; Rumana Ahmad; Anand N. Srivastava (Integrative Medicine Research)
Background: Aromatherapy is used in clinical settings for patients suffering from several chronic and critical diseases such as cancer. Ethyl acetate (EA) is a colorless liquid with a characteristic fruity smell and is naturally present in fruits and wines. Methods: In the present study, the effect of the aroma of EA was evaluated on human breast cancer cell line MDA-MB-231 and normal cell line, Vero. Cell line viability and mechanism of EA cytotoxicity were determined by Trypan blue dye exclusion assay and phase contrast microscopy. Results: It was found that EA at a concentration of 0.026 M was effective in causing considerable cytotoxicity in breast cancer cells (without even coming in contact with the culture medium and cells), while showing no effect on normal cells. Mechanism of action of EA on cancer and Vero cells was investigated by DNA fragmentation and dye binding assays using agarose gel electrophoresis (AGE) and fluorescence microscopy/cytometry, respectively. It was found that EA aroma induced predominantly necrosis in the cancer cells exposed to it. Conclusion: A study such as this has not been attempted before and results need further investigation before EA aroma can be used as a complementary therapy.